Determination of the effects of copper (Cu) and lead (Pb) heavy metals on soil carbon and nitrogen mineralizations - Kizildağ, Nacide (Penerbit Universiti Kebangsaan Malaysia, 2021)
Heavy metal (HM) pollution has become one of the most important environmental problems of the present day, as a result of the developing industrial activities. Accordingly, it is important to understand microorganism activities in soil ecosystems that have been exposed to HMs for a long time. The aim of this study was to show the potential effects of ores on soil carbon and nitrogen mineralizations which were taken from copper (Cu) and lead (Pb) mines in Balıkesir-Balya and Kastamonu-Küre districts in Turkey. The carbon (C) and nitrogen (N) mineralizations were determined by using the CO2 respiration method (30 days) and the Parnas Wagner method (42 days) under the controlled laboratory conditions (28 °C, 80% of field capacity), respectively. It was observed that carbon mineralization decreased depending on the dose increase. 250 mg kg-1 treatment with Pb was lower than the control and there was a significant difference between them (P < 0.001). In terms of nitrogen mineralization rate (%), there was no significant difference among all treatments. According to the results, Pb affected microorganisms more negatively; however, the presence of Cu slightly decreased its negative effect. It is possible to conclude that carbon mineralization can be indicator for HM pollution in the soil. However, nitrogen mineralization was not a determining factor at HM pollution in this study.